2017
DOI: 10.14260/jemds/2017/729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Magnesium Sulphate on Cardiovascular Responses During Tracheal Extubation in Patient Undergoing Craniotomies

Abstract: BACKGROUNDDuring emergence of general anaesthesia, hypertension and tachycardia caused by tracheal extubation may lead to serious complications during craniotomies. This study was designed to assess the effect of magnesium sulphate on these cardiovascular responses during extubation following craniotomies under general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The evaluated studies included data from 4303 people. 2300 of them magnesium (1114 by IV in 35 studies [6,), by epidural in 12 studies [47][48][49][50][51][52][53][54][55][56][57][58], 638 by intraperitoneal injection in 16 studies [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] and 108 by Other routes received 4 interventions. All studies compared magnesium sulfate with placebo or no drug.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluated studies included data from 4303 people. 2300 of them magnesium (1114 by IV in 35 studies [6,), by epidural in 12 studies [47][48][49][50][51][52][53][54][55][56][57][58], 638 by intraperitoneal injection in 16 studies [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] and 108 by Other routes received 4 interventions. All studies compared magnesium sulfate with placebo or no drug.…”
Section: Resultsmentioning
confidence: 99%
“…The scope of our evaluation encompassed a significant volume of data from a total of 4303 individuals. Among them, 2300 individuals received magnesium through various routes, including 1114 participants who received intravenous magnesium in 35 studies [ 10 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ], 12 studies that administered magnesium epidurally [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ] to a total of 638 participants, and 16 studies that utilized intraperitoneal injection to deliver magnesium to 638 individuals [ [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] ]. Additionally, 108 participants received magnesium through alter...…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a total of 54 clinical trials were analyzed [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [65] , [66] , [67] , [68] , [69] , 72 , 73 , 77 , 82 , 83 ], and the incidence of shivering was analyzed in different groups based on the method of magnesium administration. The results revealed that the incidence of shivering was lower in the group that received magnesium via IV injection compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations